2022
DOI: 10.3390/diagnostics12020525
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Apparent Diffusion Coefficient Distribution and Cancer Grade in Prostate Cancer and Benign Prostatic Hyperplasia

Abstract: The aim of this paper was to assess the associations between prostate cancer aggressiveness and histogram-derived apparent diffusion coefficient (ADC) parameters and determine which ADC parameters may help distinguish among stromal hyperplasia (SH), glandular hyperplasia (GH), and low-grade, intermediate-grade, and high-grade prostate cancers. The mean, median, minimum, maximum, and 10th and 25th percentile ADC values were determined from the ADC histogram and compared among two benign prostate hyperplasia (BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The inverse correlation observed between GS values and ADC min /ADC mean substantiates the assertion that as the malignancy of prostate lesions intensifies, ADC values correspondingly decline, potentially portending an unfavorable PCa prognosis. Remarkably, these conclusions are aligned with the investigations of Saito et al [ 22 ] and Bajgiran et al [ 23 ]. Within the context of lesions spanning diverse low to intermediate-risk PCa grades, both ADC min and ADC mean exhibit diagnostic value, facilitating the nuanced prediction of risk stratification pertinent to prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…The inverse correlation observed between GS values and ADC min /ADC mean substantiates the assertion that as the malignancy of prostate lesions intensifies, ADC values correspondingly decline, potentially portending an unfavorable PCa prognosis. Remarkably, these conclusions are aligned with the investigations of Saito et al [ 22 ] and Bajgiran et al [ 23 ]. Within the context of lesions spanning diverse low to intermediate-risk PCa grades, both ADC min and ADC mean exhibit diagnostic value, facilitating the nuanced prediction of risk stratification pertinent to prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…12 Previous studies have consistently demonstrated significantly lower ADC values in PCa lesions compared to benign lesions. 13,14 A meta-analysis further confirmed the diagnostic utility of ADC values, reporting the overall sensitivity of 76.9% and specificity of 77.0% for PCa detection. 15 Therefore, ADC values serve as a reliable predictive biomarker for PCa.…”
Section: Introductionmentioning
confidence: 78%
“…The restriction of free water movement within tissues can be quantified using apparent diffusion coefficient (ADC) 12 . Previous studies have consistently demonstrated significantly lower ADC values in PCa lesions compared to benign lesions 13,14 . A meta‐analysis further confirmed the diagnostic utility of ADC values, reporting the overall sensitivity of 76.9% and specificity of 77.0% for PCa detection 15 .…”
Section: Introductionmentioning
confidence: 86%
“…BPH is commonly seen in older male patients. BPH may cause bladder outlet obstruction (BOO), and therefore patients may develop a variety of symptoms related to voiding urine such as LUTS [ 1 ]. Acute urinary retention, urinary tract infection, vesicle stones and chronic kidney disease may occur if the symptoms progress.…”
mentioning
confidence: 99%